Overcoming water scarcity and quality constraints: Groundwater: Potential and Constraints - Moench, Marcus (International Food Policy Research Institute, 2001)
Groundwater problems emerging in many parts of the world reduce drought-buffer supplies, threaten environmental values, and increase risks for many of the world’s poorest people. Programs to improve public understanding and basic scientific information regarding the resource base and to encourage the evolution of groundwater management systems are essential.